2014
DOI: 10.1186/2162-3619-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia with t(7;21)(p22;q22) and 5q deletion: a case report and literature review

Abstract: The gene RUNX1 at chromosome 21q22 encodes the alpha subunit of Core binding factor (CBF), a heterodimeric transcription factor involved in the development of normal hematopoiesis. Translocations of RUNX1 are seen in several types of leukemia with at least 21 identified partner genes. The cryptic t(7;21)(p22;q22) rearrangement involving the USP42 gene appears to be a specific and recurrent cytogenetic abnormality. Eight of the 9 cases identified in the literature with this translocation were associated with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The t(7;21)(p22;q22) resulting in a RUNX1‐USP42 fusion is an infrequent abnormality found in a subcategory of myeloid malignancies. To date, 12 cases with t(7;21)(p22;q22), including 11 AML patients and one MDS (refractory anemia with excess blasts—RAEB) patient, have been reported (summarized in Table ) . Counting the present three cases, there are a total of 14 AML patients with t(7;21).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The t(7;21)(p22;q22) resulting in a RUNX1‐USP42 fusion is an infrequent abnormality found in a subcategory of myeloid malignancies. To date, 12 cases with t(7;21)(p22;q22), including 11 AML patients and one MDS (refractory anemia with excess blasts—RAEB) patient, have been reported (summarized in Table ) . Counting the present three cases, there are a total of 14 AML patients with t(7;21).…”
Section: Discussionmentioning
confidence: 90%
“…Fourteen patients were reported to have anemia (Table ). Ji et al suggested the presence of anemia in patients with t(7;21) may be due to the 5q deletion causing haploinsufficiency of the RPS14 gene at 5q33.1. Happloinsufficiency of RPS14 has been associated with erythroid differentiation and this gene was proposed as a critical gene in MDS with isolated del(5q) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B, Karyogram of 48,XY,+Y,der(7)t(3;7)(q?13;q?31),+8,t(16;21)(q24;q22)[18]/46,XY[2] by G-banding analysis. He had been diagnosed with standard-risk T-cell acute lymphocytic leukemia (T-ALL) 8.5 years earlier (95% blasts, CD2+, CD3+, CD4+, CD5+, CD8+, CD5+, CD7+, TdT++, Figure S1A).…”
mentioning
confidence: 99%
“…AML is associated with 5q abnormalities and hyperploidy [1234567]. In terms of t(6;7), this abnormality was reported in three AML cases as a mainline abnormality included in complex chromosomal abnormality [8910].…”
mentioning
confidence: 99%